A Vision of Humanistic Concern in the Poetry of Sarojini Naidu Vs. Her Poetic Style - Chouhan, Sandhya (Journal of Advanced Research in English & Education; Vol 10 No 1 (2025): Journal of Advanced Research in English and Education, 2025)
This article examines the complicated relationship between Sarojini Naidu’s profound humanistic concerns and her distinctive poetic style. Often celebrated as the “Nightingale of India”, Naidu’s poetry transcends mere aestheticism, resonating with a deep empathy for the diverse facets of Indian life, encompassing its vibrant culture, natural beauty, and the socio-political realities of her era. This study posits that Naidu’s humanistic vision, characterised by her compassion for individuals across social strata, her fervent nationalism rooted in inclusivity, and her appreciation for the delicate balance between humanity and nature, is inextricably linked to her stylistic choices. Her masterful use of vivid imagery, evocative sensory details, lyrical rhythm, and accessible diction serves not only to paint a rich tapestry of Indian life but also to amplify her underlying concerns for human dignity, unity, and freedom. Through a close reading of selected poems, this article will analyse how Naidu’s poetic techniques—including her deployment of metaphor, simile, and alliteration—effectively convey her humanistic perspectives on love, loss, patriotism, and the everyday experiences of both the privileged and the marginalised. Ultimately, this analysis seeks to illuminate how Naidu’s artistic expression serves as a powerful vehicle for her deeply felt humanistic ethos, contributing significantly to the landscape of Indian English poetry and offering enduring insights into the human condition.